Design, Synthesis, Characterization, Antiproliferative Activity, and In Silico Studies of Novel Alkyl Ether Derivatives Containing 1H‐1, 2, 4‐Triazole Ring. Issue 44 (24th November 2022) - Yilmaz, Osman; Capanlar, Seval; Akkoc, Senem; Alici, Hakan; Ozcan, Ibrahim; Tahtaci, Hakan
Abstract: In this study, starting from 1 H ‐1, 2, 4‐triazole, a new series of aliphatic ether derivatives containing phenyl and 1 H ‐1, 2, 4‐triazole groups together were synthesized using reduction and Williamson ether synthesis mechanisms, respectively. The molecular structures of the synthesized compounds were characterized by fourier‐transform infrared spectroscopy (FT‐IR), 1 H and 13 C nuclear magnetic resonance ( 1 H NMR and 13 C NMR), mass spectroscopy, and elemental analysis techniques. All synthesized compounds were screened against three different human cancer cell lines, including colon, lung, and liver cancer cells. Some of the compounds showed exceptionally high antiproliferative effects against all three cancer cell lines, with IC50 values much lower than the positive control drug bendamustine. In addition, molecular docking studies were performed to support the in vitro results and the interaction types and amino acids that play key roles in the binding of the compounds to enzymes were identified. Finally, the potential of these compounds to be drugs and their drug‐likeness properties were evaluated by absorption, distribution, metabolism, and excretion‐toxicity (ADMET) calculations and it was determined that the compounds could be drug candidates with the capacity to be effective and safe drugs for use in the treatment of different diseases. Abstract : In the present work, novel aliphatic ether derivatives containing 1 H ‐1, 2, 4‐triazole groups were synthesized. The synthesized compounds were evaluated for antiproliferative effects. According to the results of the biological activity tests, some of the synthesized compounds showed moderate to high levels of activity. The experimental and theoretical results exhibited a good coherence with each other.